2021
DOI: 10.1016/j.tcr.2021.100549
|View full text |Cite
|
Sign up to set email alerts
|

Forearm segmental bone defect: Successful management using the Masquelet Technique with the aid of 3D printing technology

Abstract: The management of forearm nonunion is challenging for orthopaedic surgeons because the forearm is a unique anatomical segment in which all the bones and structures involved embody a complex functional unit. Therefore, when treating such a complex condition, the surgeon must focus not only on bone healing but also on the restoration of the native anatomy in order to replicate the normal relationship between the bones and all the surrounding structures and thus the full function of the forearm, the elbow and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…Masquelet's technology has been popular in recent years. It has been reported for the treatment of segmental bone defects of the humerus, ulnar, and femur, but seems not the indications of intra-articular bone defects 7,16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masquelet's technology has been popular in recent years. It has been reported for the treatment of segmental bone defects of the humerus, ulnar, and femur, but seems not the indications of intra-articular bone defects 7,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 9 Several reports have described bone defect reconstruction surgery using the Masquelet-induced membrane technique. 7 , 16 , 17 However, it is mainly used for segmental bone defects and has not been used for intra-articular bone defects. 2 Iliac crest grafting is a routine treatment for bone defects, but due to the special anatomical shape of the distal humerus, it is difficult to obtain the appropriate shape and size of the iliac crest.…”
mentioning
confidence: 99%
“…Walker et al [ 33 ] demonstrated successful use of this method in forearm nonunion for defects up to 5.4 cm in size. Pachera et al [ 34 ] reported a case of a 53-year-old patient with a left forearm deformity due to an atrophic nonunion of the ulna and a malunion of the radius, which was successfully managed with the use of the Masquelet technique associated with a corrective osteotomy of the radius, performed with the aid of a 3D model. Potential problems with the Masquelet technique include loosening of the fixation implant, infection, fracture through the graft, and bone resorption.…”
Section: Adult Forearm Nonunion Surgical Treatmentmentioning
confidence: 99%
“…Guías quirúrgicas a medida Tratamiento de las deformidades angulares del antebrazo con guía quirúrgica para osteotomía paciente-específica [129][130][131] Adquisición de la imagen: TAC de ambos antebrazos, incluyendo codo y muñeca. Se realiza 4-6 semanas pre-intervención.…”
Section: Aplicaciones De La Impresión 3d En El Antebrazo Y La Muñecaunclassified
“…Esta guía es más sencilla e incluye dos ranuras para la sierra oscilante y orificios para las agujas de Kirschner que unen la placa al hueso. 129 Figura 100. Diseño de la guía quirúrgica de Vlachopoulos.…”
Section: Aplicaciones De La Impresión 3d En El Antebrazo Y La Muñecaunclassified